A visco-plastic framework for interface processes in sedimentary reservoir rocks at HPHT conditions. (May 2020) - Sari, Mustafa; Alevizos, Sotiris; Poulet, Thomas; Lin, Jack; Veveakis, Manolis
Abstract: As energy operations face the challenge of reservoirs at ever-increasing depths, modelling the response of reservoir rocks at high pressure and high temperature (HPHT) conditions is a crucial step for successfully unlocking new resources. At these conditions, rocks can experience thermal and pressure sensitivity, as well as admit internal phase changes at the pore-solid interfaces that determine their macroscopic response to external loading. It is therefore expected that constitutive laws of Geomechanics should be enriched to accommodate such effects. In this work, a multi-physics constitutive theory for sedimentary rocks is proposed within the general framework of viscoplasticity. The viscosity of the material is assumed to be a function of the temperature, pore-pressure and energy required to alter the inter-granular interfaces. This energy is expressed through the chemical potentials of the phases involved during processes like chemical dissolution/precipitation of the interfaces or mechanical debonding. The resulting flow law and corresponding stress equilibrium are coupled to the energy and mass conservation laws, constituting a closed system of equations, which is solved using the Finite Element simulator REDBACK. A series of numerical tests for performance and calibration is then successfully performed against different types of reservoir rocks, confining pressures and temperatures (from room temperature to over 800K). We show that the mechanical response of sedimentary porous rocks at strains usually achieved in laboratory testing can be explained by accounting for the interface processes taking place at the cementitious material bonding the grains, a process that can also determine the brittle-to-ductile transition of sedimentary rocks. Highlights: We suggest a multi-physics framework, whereby the hardening law of plasticity is a function of temperature, pressure, chemical potentials. The evolution laws of the state variables are the governing laws for mass and energy balance. Effects of interface processes are included through the internal enthalpy of the system. Validation against multi-physics tests in different materials, shows remarkable agreement.